2018
DOI: 10.1021/acs.chemmater.8b02614
|View full text |Cite
|
Sign up to set email alerts
|

Li-Substituted Layered Spinel Cathode Material for Sodium Ion Batteries

Abstract: The O3-type layered Na(NixFeyMnz)O2 (0 < x, y, z < 1) cathode materials have attracted great interest in sodium-ion batteries due to the abundance and cost of raw materials and their high specific capacities. However, the cycling stability and rate capability at high voltages (> 4.0V) of these materials remains an issue. In this work, we successfully synthesized a Li-substituted layered-tunneled (O3-spinel) intergrowth cathode (LS-NFM) to address these issues. The remarkable structural compatibility and connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 74 publications
0
29
1
Order By: Relevance
“…Improved rate capability on the other hand could be ascribed to the improved charge transport kinetics due to direct connection between the 3D channels in the spinel phase and 2D channels in the layered phase modifying the diffusion pathway. 166 A highly reversible transition at high voltages was also reported for the layered-tunnel intergrowth structure with the composition Na 0.6 MnO 2 . 167 The highly reversible P2/tunnel to OP4/tunnel phase transition was detected using in situ XRD upon cycling the composite up to 4.3 V. Taking this further and combining P2, P3 and spinel structures to form the Na 0.5 [-Ni 0.2 Co 0.15 Mn 0.65 ]O 2 nanocomposite, Hou et al were able to synthesise a particularly stable composition for which no phase transitions were detected via ex situ XRD when cycled between 1.5 and 4.0 V vs. Na/Na + .…”
Section: Mixed Phase Materialsmentioning
confidence: 73%
See 1 more Smart Citation
“…Improved rate capability on the other hand could be ascribed to the improved charge transport kinetics due to direct connection between the 3D channels in the spinel phase and 2D channels in the layered phase modifying the diffusion pathway. 166 A highly reversible transition at high voltages was also reported for the layered-tunnel intergrowth structure with the composition Na 0.6 MnO 2 . 167 The highly reversible P2/tunnel to OP4/tunnel phase transition was detected using in situ XRD upon cycling the composite up to 4.3 V. Taking this further and combining P2, P3 and spinel structures to form the Na 0.5 [-Ni 0.2 Co 0.15 Mn 0.65 ]O 2 nanocomposite, Hou et al were able to synthesise a particularly stable composition for which no phase transitions were detected via ex situ XRD when cycled between 1.5 and 4.0 V vs. Na/Na + .…”
Section: Mixed Phase Materialsmentioning
confidence: 73%
“…An improved performance in terms of capacity and average voltage was found for the O3 layered/spinel composite Na 0.87 -Li 0.25 Ni 0.4 Fe 0.2 Mn 0.4 O 2+d electrode. 166 The voltage prole of the composite material shows a reversible high voltage plateau while this plateau is irreversible in the spinel free material, suggesting that addition of the spinel phase contributed towards the enhanced structural and electrochemical stability, especially at high voltages, the mechanism of which is yet to be explored. Improved rate capability on the other hand could be ascribed to the improved charge transport kinetics due to direct connection between the 3D channels in the spinel phase and 2D channels in the layered phase modifying the diffusion pathway.…”
Section: Mixed Phase Materialsmentioning
confidence: 98%
“…X‐ray absorption near edge structure (XANES) spectra were recorded at the Fe K‐edge of MCFO NS, MFO NS, CFO NP, and other compounds (Figure 3b ). [ 28 , 29 ] The XANES spectra of FeO and Fe 2 O 3 show that white line intensities are located at 7127.8 and 7132.5 eV, corresponding to Fe 2+ and Fe 3+ , respectively. Among the various spinel oxides, CFO NP exhibits a white line intensity at 7132.4 eV, demonstrating that the valence state of Fe in CFO NP is the highest, which is close to Fe 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…O 3−Fdtrue3¯ m Category : Recently, Xiong and co‐workers successfully integrated spinel structure with O3‐layered structure to obtain an intergrowth composite of Na 0.87 Li 0.25 Ni 0.4 Fe 0.2 Mn 0.4 O 2+d (LS–NFM) via Li + substitution and careful optimization of Na + /Li + ratio . It was reported that the O3 phase did not form at high Na + content, while formation of separate spinel phases is more favorable when the Li + content is too high.…”
Section: Sibsmentioning
confidence: 99%
“…c) Cyclic performances and d) rate capabilities of LS–NFM and single‐phase undoped NFM cathode; log DNa+ plots during the e) charge and f) discharge process. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Sibsmentioning
confidence: 99%